Modern management practices of cultural policy in a regional cluster - A. S. Plyachotko, E.M. Akulich, L. G. Szkulmovskaya, L.V. Shatskih, (Opción, 2019)
The research objective is to develop methodological provisions for increasing the cultural and art institutions’ efficiency in terms of their exposure to the social-economic development of a regional cluster via the systemic method, the dialectic method, comparative-historical method and structural-functional analysis. The results of the study lie in the disclosure of the essential characteristics of modern practices of managing cultural policy in the context of a regional cluster. In conclusion, modern socio-cultural practices of the regional cultural policies management can effectively influence positive achievements in the socio-economic development of the region.